Application of ionic liquids for charge transport improvement in perovskite solar cells. (2022) - Aidarkhanov, Damir; Daniyeva, Nurgul; Ng, Annie
Abstract: The hybrid organic–inorganic perovskite solar cells (PSCs) exhibit a huge potential in the photovoltaic (PV) community due to a number of outstanding properties of the perovskite materials. Despite the device efficiencies of PSCs approaching to those based on crystalline silicon, this emerging PV technology still needs to overcome several bottlenecks including material stability and device lifetime. One of the strategies is the replacement of TiO2 electron-transport layer with SnO2, which has a lower photocatalytic effect and requires lower processing temperatures. The current work demonstrates an effective surface treatment of SnO2 electron-transport layer (ETL) by the application of 1-ethyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide (EMPTFSI) ionic liquid (IL). The characterization results indicate a significant improvement of charge extraction efficiency at the interface of ETL/perovskite after the IL surface treatment, resulting in an enhancement of the power conversion efficiency (PCE) of PSCs from 18.1% to 19.3%. The obtained preliminary results will be discussed in this paper.